PENINGKATAN AKTIVITAS DAN HASIL BELAJAR SISWA MELALUI PENERAPAN PEMBELAJARAN DEMONSTRASI PADA MATA PELAJARAN IPS KOMPETENSI DASAR KEGIATAN PELAKU EKONOMI DI MASYARAKAT KELAS VII MTs SABDARIA NADA SEMESTER GANJIL - Nursalam Nursalam (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2015)
Demonstration learning method implemented to make students can actively and creatively in solving problems in learning activities so that there is a balance and integration between cognitive, affective, and psychomotor. The purpose of this studywas to describe how the implementasion of a demonstration learning method in social science subject on basic competency the activities of economic actors in society. The approach of this study was qualitative approach with classroom action research. The object of this study is students of class VII odd semester. This study was conducted with two cycles. From the summary result of this study for student’s learning outcomes, showed improvement from the first cycle to the second cycle. Daily test scores of student in the second cycle reaches 85% with “Very Active” criteria. This value has suited with individually and classical learning mastery criteria, which are ≥70 and 85%. Student whose grades in accordance with KKM were 32 student (90%). The application of demonstration learning method can increases students’ cognitive abilities, through activities that students can interact in discussion groups that allow students to exchange ideas to remember and understand the material.